2021
DOI: 10.3389/fnut.2021.780205
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and COVID-19 Susceptibility and Severity: A Mendelian Randomization Study

Abstract: Background: Carnitine, a potential substitute or supplementation for dexamethasone, might protect against COVID-19 based on its molecular functions. However, the correlation between carnitine and COVID-19 has not been explored yet, and whether there exists causation is unknown.Methods: A two-sample Mendelian randomization (MR) analysis was conducted to explore the causal relationship between carnitine level and COVID-19. Significant single nucleotide polymorphisms from genome-wide association study on carnitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…We are currently not accounting for microbial metabolic activity, but it would be a valuable extension of the current effort as it also permits elucidate host-microbiome co-metabolism [21] . Moreover, in our models, the availability of carnitine and its derivative was limited by the defined diet uptake, while carnitine and associated lipids have been reported to change with infection and disease severity [67] . Similarly, biotin [68] is increased in COVID patients.…”
Section: Discussionmentioning
confidence: 80%
“…We are currently not accounting for microbial metabolic activity, but it would be a valuable extension of the current effort as it also permits elucidate host-microbiome co-metabolism [21] . Moreover, in our models, the availability of carnitine and its derivative was limited by the defined diet uptake, while carnitine and associated lipids have been reported to change with infection and disease severity [67] . Similarly, biotin [68] is increased in COVID patients.…”
Section: Discussionmentioning
confidence: 80%
“…The modules identified various proteins and metabolites involved in inflammatory and vascular injury processes, such as MMP 12, Cathepsin D and RAGE which, to the best of our knowledge, have not yet been studied as targets for therapeutic intervention in COVID-19. Of note, our modules contained IL-6, which is already a mainstay of treatment for severe disease (Brown et al, 2021), and several other molecules such as carnitine, niacinamide and IFN-gamma which others have been studying in the context of COVID-19 therapies (Li et al, 2021;van Laarhoven et al, 2021;Fu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Increased percentage of oxygen saturation as a result of L-carnitine supplementation in patients can accelerate the recovery of symptoms. This improved oxygen saturation may be due to decreased ACE2 expression and thus inhibition of virus binding to lung cells [ 18 ]. In this regard, Bellamine et al showed that L-carnitine can reduce the expression of ACE2 in human pulmonary epithelial cells in vitro as well as in clinical conditions in animal models and humans [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the carnitine level of the body is negatively correlated with COVID-19 susceptibility and severity. So, an increase in the carnitine amount was associated with lower vulnerability to COVID-19 [ 18 ]. Also, another study used a combined metabolic activators regimen that included l-carnitine, and results showed that treating patients with this regimen accelerate the recovery period of COVID-19 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%